Differential Outcomes in Agency-Based Mental Health Care Between Minority and Majority Youth. (May 2016) - Patterson, David A.; Dulmus, Catherine N.; Maguin, Eugene; Perkins, Jacob
Background: Childhood mental health problems represent a significant public health concern globally. There is a converging discussion among researchers and practitioners alike that the research results of effectiveness studies are not fully generalizable and applicable to ethnoracial minority groups in real-world practice settings. Methods: Archival data on discharges from eight residential programs for children and youth aged 5–18 and operated by a large, child and family human services agency were analyzed to identify the relationship between client demographics and treatment outcomes. Results: Minority status was associated with lower odds of treatment success and higher odds of disengagement from treatment. Discussion: The results found that minority youth in residential programs had less favorable outcomes, in terms of both disengagement from treatment and a successful discharge, than White youth. This study calls into question whether current treatments are reaching and best serve ethnoracial minority groups in real-world practice settings.